2012
DOI: 10.1021/jz2016654
|View full text |Cite
|
Sign up to set email alerts
|

Ionization of Water Clusters Mediated by Exciton Energy Transfer from Argon Clusters

Abstract: The exciton energy deposited in an argon cluster (Ar n , ⟨n = 20⟩) using VUV radiation is transferred to softly ionize doped water clusters ((H2O) n , n = 1–9), leading to the formation of nonfragmented clusters. Following the initial excitation, electronic energy is channeled to ionize the doped water cluster while evaporating the Ar shell, allowing identification of fragmented and complete water cluster ions. Examination of the photoionization efficiency curve shows that cluster evaporation from excitons loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
41
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 46 publications
4
41
0
Order By: Relevance
“…This observation is independent of the ionization method, whether electron-or photoionization is implemented [26]. The 20 non-protonated (H 2 O) + n ions were observed upon ionization of water clusters solvated with rare gas atoms [20,21,27,28,29]. Nevertheless, an infrared spectroscopy of the water clusters showed that the non-protonated clusters have the structure H 3 O + · · ·OH·, i.e., the proton transfer still takes place [30,31].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…This observation is independent of the ionization method, whether electron-or photoionization is implemented [26]. The 20 non-protonated (H 2 O) + n ions were observed upon ionization of water clusters solvated with rare gas atoms [20,21,27,28,29]. Nevertheless, an infrared spectroscopy of the water clusters showed that the non-protonated clusters have the structure H 3 O + · · ·OH·, i.e., the proton transfer still takes place [30,31].…”
Section: Introductionmentioning
confidence: 90%
“…In many laboratory studies water clusters are detected by mass spectrometric methods. Therefore the 10 cluster ionization is of prime importance and was investigated by various means [15,16,17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…13 Several groups have studied ground state cationic water clusters (H 2 O) + n in experiment. [14][15][16][17] Studying these clusters in experiment is challenging since the unprotonated cluster ions are formed in a highly excited vibrational state. 18,19 This leads to fragmentation of the water clusters on an ultrafast time scale to give rise to protonated species.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 This leads to fragmentation of the water clusters on an ultrafast time scale to give rise to protonated species. 20 However, several studies have measured unprotonated cationic water clusters, [14][15][16][17] and recently the infrared spectroscopy of size selected unprotonated cationic water clusters was reported. 16 In these clusters, there is the possibility of several distinct structural motifs, which are illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Many papers have been published on water clusters, mainly aiming for the possibility of using them as a vehicle for systematically studying molecular properties of water [4][5][6][7][8][9]. Nevertheless, not all is known about the different-size water clusters formation and ionization.…”
Section: Introductionmentioning
confidence: 99%